A brief overview on grain growth of bulk electrodeposited nanocrystalline nickel and nickel-iron alloys - Ni Haitao; Zhu Jiang; Wang Zhaodong; Lv Haiyang; Su Yongyao; Zhang Xiyan (Reviews on Advanced Materials Science, 2019)
This review focuses on grain growth behaviors and the underlying mechanisms of bulk electrodeposited nanocrystalline nickel and nickel-iron alloys. Effects of some important factors on grain growth are described. During thermal-induced grain growth process, grain boundary migration plays a key role. For similar thermal conditions, due to grain boundary mobility with solute drag, limited grain growth occurs in nanocrystalline alloys, as compared to pure metals. Nonetheless, in the case of stress-induced grain growth process, there are a variety of mechanisms in samples having various deformation histories. As an example the grain growth of nanocrystalline nickel and Ni-20%Fe alloy with nearly the same grain-size distribution and average grain size is compared in this paper. Thermal analysis indicates nanocrystalline nickel is much more prone to rapid grain growth than nanocrystalline Ni-20%Fe alloy. Nevertheless, grain growth of nanocrystalline Ni-20%Fe is found to be more pronounced than nanocrystalline nickel during rolling deformation.